2006
DOI: 10.1002/pat.741
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanical and dynamic mechanical properties of thermotropic liquid crystalline polymer/unsaturated polyester/glass fiber in situ hybrid composites

Abstract: In situ hybrid composites of thermotropic liquid-crystalline polymer (TLCP), unsaturated polyester (UP) and glass fiber (GF) have been successfully prepared by melt mixing technology. The mechanical properties and dynamic mechanical properties and the morphologies of these in situ hybrid composites have been studied by static mechanics analysis, dynamic mechanical analysis (DMA) and scanning electron microscopy (SEM). The static mechanical test results showed that the impact strength and the bending strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…This phenomenon might be attributed to the introduction of CEPPA, which catalyzed char formation; the char in turn inhibited the combustion and decomposition of PET, and this enhanced the LOI value and UL-94 rating. 17 The LOI values of the PET/nano-ZnCO 3 composites slightly increased with the nano-ZnCO 3 content increasing up to 3 wt %; when 3 wt % nano-ZnCO 3 was added to the PET matrix, the LOI value increased from 23 to 25%. The LOI values of the PET/nano-ZnCO 3 composites were nearly the same as the value of pure PET.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This phenomenon might be attributed to the introduction of CEPPA, which catalyzed char formation; the char in turn inhibited the combustion and decomposition of PET, and this enhanced the LOI value and UL-94 rating. 17 The LOI values of the PET/nano-ZnCO 3 composites slightly increased with the nano-ZnCO 3 content increasing up to 3 wt %; when 3 wt % nano-ZnCO 3 was added to the PET matrix, the LOI value increased from 23 to 25%. The LOI values of the PET/nano-ZnCO 3 composites were nearly the same as the value of pure PET.…”
Section: Resultsmentioning
confidence: 93%
“…Pure PET had an LOI value of only 23% and a V2 rating according to the UL‐94 test, whereas PET60, which contained 0.6 wt % phosphorus, had a much higher LOI value (29%) and reached a V0 rating; this indicated that phosphorus had a significant effect on the improvement of the flame retardancy of PET. This phenomenon might be attributed to the introduction of CEPPA, which catalyzed char formation; the char in turn inhibited the combustion and decomposition of PET, and this enhanced the LOI value and UL‐94 rating 17. The LOI values of the PET/nano‐ZnCO 3 composites slightly increased with the nano‐ZnCO 3 content increasing up to 3 wt %; when 3 wt % nano‐ZnCO 3 was added to the PET matrix, the LOI value increased from 23 to 25%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 In addition, the mechanical properties are enhanced. 37 In addition, the mechanical properties are enhanced.…”
Section: In Situ Compositesmentioning
confidence: 99%